Afroeuropean Mobilities in Francophone African Literatures - Toivanen, Anna-Leena.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
"Engaging Francophone African literary texts, this book challenges reductive readings of postcolonial mobility in migration and diaspora studies. Its complex framing of Afroeuropean mobilities surfaces educational, professional, leisure, urban and other mobilities obscured by otherwise dominant imaginaries of the clandestine African migrant." $1 (BPolo B. Moji, Author of Gender and the Spatiality of Blackness in Contemporary AfroFrench Narratives (2022), University of Cape Town, South Africa "This is the first book to bring together the new mobilities paradigm with postcolonial African literature. Toivanen deftly analyses a wide range of embodied experiences, spaces, vehicles and creative practices of mobility within Afroeuropean fiction. From clandestine migration to everyday commuting, from tourism to diasporic return, she opens a refreshed mobile perspective on a rich body of Francophone literature that will be of great interest to both mobility scholars and literary scholars." $1 (BMimi Sheller, Dean of The Global School, Worcester Polytechnic Institute, USA This open access book contributes to the mobility humanities from the perspective of postcolonial literary mobilities and aims at enhancing dialogue between mobilities research and postcolonial literary studies. The study produces new perspectives on Afroeuropean mobilities in Francophone African and Afrodiasporic literatures from the mid-twentieth century to the present, covering a wide set of texts across literary genres. Focusing on representations of educational travel, tourism, diasporic returns, work-related mobilities, and clandestine migratory journeys, Toivanen examines portrayals of mobility practices and modes of transport to map out the meanings of embodied (im)mobilities in the Afroeuropean context. In addition to thematic analysis, the volume also explores the manifestations of mobility in literary form. Anna-Leena Toivanen is an Academy Research Fellow at the University of Eastern Finland. She is the author of Mobilities and Cosmopolitanisms in African and Afrodiasporic Literatures (2021) and co-editor of Urban Mobilities in Literature and Art Activism (2024).s
Chapter 1: Introduction -- Chapter 2: Educational mobilities in the metropolis -- Chapter 3: Mobilities of African and Afroeuropean leisure travelers -- Chapter 4: Mobile (3z(Bhomecomings(3y (Bfrom Europe to Africa -- Chapter 5: Work, labor, and Afroeuropean (im)mobilities -- Chapter 6: Clandestine Afroeuropean itineraries.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: African literature; European literature; Literature, Modern -- 20th century; Literature, Modern -- 21st century; African Literature; European Literature; Contemporary Literature